Activation of Kaolin Minerals from Ketapang Regency as Cu Metal Adsorbent Material - Septiansyah, Sy. Indra; Afandi, Idris Herkan; Dirtami, Retno Tasya (BRIN Publishing, 2022)
Kaolin is a term given to a group of phyllosilicate minerals whose layers have a 1:1 structure with Al2Si2O5(OH)4 composition. This type of kaolin phyllosilicate mineral is commonly known as a clay mineral. The kaolin clay group consists mainly of the kaolinite mineral or better known as white clay. Kaolin is widely applied in industries such as paper, ceramics, rubber, plastic, paint, fiberglass, cosmetics, etc. The processing of kaolin as an adsorbent can be carried out using physical activation, where the kaolin is washed and separated from the impurities and dried into a powder. Then the chemical activation of kaolin will go through a leaching process using HCl with optimal concentrations aimed at separating kaolin from impurities that are still chemically bound to kaolin. The results of the characteristics show recovery of 71.42% to 81.2% and moisture content <2%. The chemical composition of kaolin containing SiO2 was 53.32–67.32%, Al2O3 was 28.22–30.47%, Fe2O3 was 1.32%, CaO was 0.03%, MgO was 0.20%, MnO2 was 0.01%, K2O of 0.86%, NaO of 0.01%, Cr of 0.01%, LOI of 11.03%. The adsorption test results on Cu metal in CuSO4 solution showed the absorption of 62–93% of Cu metal which was adsorption.